Exploring Multiple Primary Malignancies: An Institutional Experience with Dual Malignancy Cases - PK, Kiran; Prakash, G Hari; KR, Sahana; Naik, Radheshyam (Asian Pacific Journal of Cancer Care, 2024)
Objective: To determine the incidence, clinical characteristics, and survival outcomes of patients with multiple primary malignancies at a tertiary care cancer centre. Methods: A retrospective analysis of 28 patients (11 males, 17 females) with histologically confirmed multiple primary malignancies was conducted from 2020 to 2022. Data on demographic characteristics, tumour sites, histopathology, staging, and survival were collected. Kaplan-Meier method was used for survival analysis with log-rank tests for group comparisons. Results: The incidence of multiple primary malignancies was 0.73%. Metachronous tumours (67.9%) were more common than synchronous tumours (32.1%). Breast cancer was the most frequent primary (32.1%) and secondary (28.6%) malignancy. Mean survival time significantly differed between males (198.0 months, 95% CI: 76.8-122.4) and females (125.2 months, 95% CI: 88.5-162.0, p=0.093). Advanced stage presentation was common, with 42% of primary and 25% of secondary tumours diagnosed at stage III. The event-free survival was higher for metachronous than synchronous malignancies (log-rank p<0.05). Among patients, 28.6% had a positive family history, and 17.9% reported substance addiction. Conclusion: Multiple primary malignancies show distinct patterns in incidence, tumour site distribution, and survival outcomes, with metachronous presentations and breast cancer predominance being key characteristics in our population.